Carry-Over Quality of Pre-acclimatization to Altitude Elicited by Intermittent Hypoxia: A Participant-Blinded, Randomized Controlled Trial on Antedated Acclimatization to Altitude - Treml, Benedikt; Kleinsasser, Axel; Hell, Tobias; Knotzer, Hans; Wille, Maria; Burtscher, Martin (Frontiers in Physiology, 2020)
Intermittent normobaric hypoxia (IH) is increasingly used to pre - acclimatize for a sojourn to high altitude. There is a number of hypoxia - protocols observing the hypoxic ventilatory response (HVR), but little is known about the carry - over quality of the Lake Louise Score (LLS). We thus studied a week - long, one hour per day poikilocapnic hypoxia protocol on whether acclimatization could be carried over for one week. Rationale for this was that it usually takes one week to get from Europe, Britain or the USA to the base camp of a major mountain. Forty-nine healthy volunteers of both sexes were exposed to daily bouts of 1 hour at an inspiratory fraction of oxygen (FiO2) of 0.11 or 0.21 (control) for 7 consecutive days. Seven days after cessation of IH or sham exposures participants were again subjected to hypoxia (FiO2 = 0.11) for 6 hours and measurements of isocapnic HVR and blood gases out of the arterialized earlobe were taken and LLS was assessed. In those with IH exposures LLS was reduced which was not the case in those with sham exposure (87% vs. 50%). Changes in HVR or the arterial hemoglobin saturation were not observed. Gender neither affected LLS nor HVR nor blood gases or carry -over quality. We found that our week - long, hypoxia protocol grants a reduction in LLS that can be carried over the time span of one week. In this way, antedated acclimatization may improve safety and comfort on the mountain.